Does Fiscal Monitoring Make Better Governments? Evidence from U.S. Municipalities - Nakhmurina, Anya (The Accounting Review, 2024)
ABSTRACT This paper examines the effect of state-level monitoring on municipal governance, focusing on outcomes in financial reporting quality, local corruption, political entrenchment, and municipal financial soundness. I exploit the staggered adoption of fiscal monitoring policies that entail a regular review of municipal financial reports for signs of fiscal distress. I find that introducing these monitoring policies is associated with an increase in the proxies for reporting quality, a decrease in the number of corruption convictions, and a reduction in re-election likelihood for incumbent politicians. Consistent with the purpose of the policies, my evidence shows that fiscal health ratios of municipalities improve after initiating state monitoring. Collectively, my results are consistent with state fiscal monitoring improving several important aspects of municipal governance. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G18; G38; H1; H11; H7; H83; M4.